2021
DOI: 10.1371/journal.pone.0246991
|View full text |Cite
|
Sign up to set email alerts
|

The impact of information about different absolute benefits and harms on intention to participate in colorectal cancer screening: A think-aloud study and online randomised experiment

Abstract: Background There is considerable heterogeneity in individuals’ risk of disease and thus the absolute benefits and harms of population-wide screening programmes. Using colorectal cancer (CRC) screening as an exemplar, we explored how people make decisions about screening when presented with information about absolute benefits and harms, and how those preferences vary with baseline risk, between screening tests and between individuals. Method We conducted two linked studies with members of the public: a think-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
1
10
1
Order By: Relevance
“…This is consistent with results from a survey about the intention to attend bowel cancer screening, where most people were not influenced by the absolute benefits and harms presented. 33 In contrast to other studies, we did not observe a focus on the negative implications of a high-risk classification (such as distress, potential pressure for lifestyle changes or the burden of being highrisk for multiple cancer types). 28,34 Reduction in the potential harms of screening for those at low risk was also not a consideration, emphasizing that this may be of greater concern for researchers and clinicians than the public.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 99%
See 2 more Smart Citations
“…This is consistent with results from a survey about the intention to attend bowel cancer screening, where most people were not influenced by the absolute benefits and harms presented. 33 In contrast to other studies, we did not observe a focus on the negative implications of a high-risk classification (such as distress, potential pressure for lifestyle changes or the burden of being highrisk for multiple cancer types). 28,34 Reduction in the potential harms of screening for those at low risk was also not a consideration, emphasizing that this may be of greater concern for researchers and clinicians than the public.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 99%
“…While evidence was necessary to support their decision, risk stratification was viewed favourably if there was any benefit. This is consistent with results from a survey about the intention to attend bowel cancer screening, where most people were not influenced by the absolute benefits and harms presented 33 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…14 In addition, a majority of participants asked about willingness to take up colorectal screening stated that they would accept the offer if at 1%, 3%, or 5% 15-year risk, although participants were more likely to be willing to take up an offer if at higher risks. 25 There are also encouraging findings to suggest that receiving information on risk status does not cause large negative reactions. For example, Emmons et al 26 found that 33% of participants reported lower worry after completing colorectal cancer risk assessment and Trevena et al 27 found no difference in anxiety between targeted colorectal cancer risk information and generic information on colorectal cancer screening.…”
Section: Effects Of Risk-adaptive Screening On Uptakementioning
confidence: 98%
“… 14 In addition, a majority of participants asked about willingness to take up colorectal screening stated that they would accept the offer if at 1%, 3%, or 5% 15-year risk, although participants were more likely to be willing to take up an offer if at higher risks. 25 …”
Section: Effects Of Risk-adaptive Screening On Uptakementioning
confidence: 99%